- PERAN OMBUDSMAN REPUBLIK INDONESIA DALAM MELAKSANAKAN PENGAWASAN TERHADAP PERALIHAN STATUS ANGGOTA KOMISI PEMBERANTASAN KORUPSI MENJADI PEGAWAI APARATUR SIPIL NEGARA ATAU PEMERINTAH : - - Abel Sheva Xavier Istiadi; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2023)
The Government of Indonesia seeks to establish a state institution that has authority to oversee delivery of public services. The Ombudsman is a public service institution formed at the initiation of Government through Presidential Decree No. 44 of 2000 concerning the National Ombudsman Commission to become forum for building public trust to create an honest, clean, open government and free from corruption, collusion and nepotism to create an effective and efficient government. The problem in this research relates to the transfer of status from KPK employees to ASN. It is suspected that there are maladministration activities in the process of transferring the status. Research method is normative juridical research with statutory approach that used qualitative descriptive analysis. The results of this study indicate that mechanism for issuing a recommendation letter is given to the Head of KPK and the Head of the State Civil Service Agency, the Ombudsman RI is in accordance with the procedures regulated by the rule of law, especially those listed in the Ombudsman RI Law. The Ombudsman basically cannot follow up on reports listed with Number 625 in 2021 which contains findings of maladministration from public services. Particularly on the fault of the public service